Attitude of Science and Technology Education Lecturers and Students Towards Using Metacognitive Strategies in Colleges of Education in North-East Nigeria - Adamu, J. G.,; Abdullahi, , A. B.; Abani, , F. S. (Kashere Journal of Education, 2021)
The study investigated the attitude of lecturers and students of Science Technology Education and Mathematics (STEM) towards metacognitive learning strategies in Colleges of Education in North[1]East Zone of Nigeria. One purpose was identified, one research question answered and one null hypothesis tested. The study employed descriptive survey research design in which a 16-item instrument, designed by the researchers, was used in collecting data from a sample of 138 respondents were randomly selected, made up of 56 lecturers and 82 students, drawn from 10 Colleges of Education in the North-East Zone. The instrument was validated by two experts in Science Education, drawn from Department of Education, University of Maiduguri. The validated copy was pilot tested on 25 students and 10 lecturers of Science Education programme from Sa’adatu Rimi College of Education, Kano, an institution outside the study area. Test re-test method was used to obtain the reliability of the instrument, using the Pearson Product Moment Correlation Coefficient (r) which stood at 0.87. Mean and standard deviation were used in analyzing and answering the research question. The null hypothesis was tested at 0.05 level of significance using the z-test. The study found that students of Science Technology Education and Mathematics (STEM) in Colleges of Education in the North-East Zone of Nigeria had a positive attitude towards metacognitive learning strategies. The study also found that there was no significant difference between the mean scores of the responses of lecturers and students on the students’ attitude towards metacognitive learning strategies in Colleges of Education in North-East Zone of Nigeria. It recommended among others, that Students of STEM in Colleges of Education in North-East Zone should continuously develop positive attitude towards metacognitive learning strategies which have the tendency to improve their performances, and methods should be put in place by lecturers and management of the Colleges of Education to design programmes, activities and schedules which are able to arouse students’ interest in metacognition and as well sustain such interest